Rooting ability of leafy-stem cuttings of hybrid Shorea (Dipterocarpaceae) - Kenzo, T. (2020)
Although cutting is a useful method for vegetative propagation and tree breeding, there is a difference in rooting ability between tree species and even between node positions within a species. A large number of F1 hybrids of Shorea (Shorea curtisii × S. leprosula) (Dipterocarpaceae) have recently been found in Singapore. Given that some of the hybrid traits appear to have higher physiological performances than those of their parent species, understanding the rooting ability of the leafy-stem cuttings of F1 hybrids may contribute to performance improvement in dipterocarp trees. In this study, we compared the rooting abilities of cuttings taken from seedlings of F1 hybrids and their parent species at different node positions. The cuttings of F1 hybrids showed rooting ability with small internode differences, and the rooting rate (32.2%) was almost intermediate between those of S. curtisii (42.0%) and S. leprosula (21.0%). The rooting rates of hybrids and parents fell into the middle range of previously reported values for 21 closely related Shorea species. Overall, the rooting ability of F1 hybrids is comparable with that of their parent species and/or other Shorea species in the red meranti group. Thus, F1 hybrids could be mass propagated through cuttings.